Approximate Periodic Solution for the Nonlinear Helmholtz-Duffing Oscillator via Analytical Approaches. (29th September 2014) - Mirzabeigy, A.; Yazdi, M. K.; Nasehi, M. H.
Abstract : The conservative Helmholtz-Duffing oscillator is analyzed by means of three analytical techniques. The max-min, second-order of the Hamiltonian, and the global error minimization approaches are applied to achieve natural frequencies. The obtained results are compared with the homotopy perturbation method and numerical solutions. The results show that second-order of the global error minimization method is very accurate, so it can be widely applicable in engineering problems.